2004
DOI: 10.1002/dvdy.20137
|View full text |Cite
|
Sign up to set email alerts
|

Innervation‐dependent and fiber type‐specific transcriptional regulation of the slow myosin heavy chain 2 promoter in avian skeletal muscle fibers

Abstract: Skeletal muscle fiber type is regulated, in part, by innervation leading to transcriptional regulation of fiber typespecific genes. Here, we report the initial characterization of the transcriptional regulation of the slow myosin heavy chain 2 (MyHC2) promoter in innervated and noninnervated slow medial adductor (MA) and fast pectoralis major (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 62 publications
(40 reference statements)
2
50
0
Order By: Relevance
“…During in vivo fetal muscle development, however, the local environment (extrinsic to muscle cells) plays a deciding role in modulating the final fiber types eventually displayed by the myotubes (Dunglison et al, 1999;Hughes, 1999;Robson and Hughes, 1999). Innervation is undoubtedly an important part of the extrinsic regulatory mechanism, which has been shown both in vivo (McLennan, 1994;Lefeuvre et al, 1996;Washabaugh et al, 1998), as well as in vitro using co-cultures of the nerve and myotubes (Jiang et al, 2004;Jordan et al, 2005). In addition, maturation and survival of both primary and secondary myotubes are largely dependent on innervation (Hughes and Ontell, 1992;Ashby et al, 1993a,b;Wilson and Harris, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During in vivo fetal muscle development, however, the local environment (extrinsic to muscle cells) plays a deciding role in modulating the final fiber types eventually displayed by the myotubes (Dunglison et al, 1999;Hughes, 1999;Robson and Hughes, 1999). Innervation is undoubtedly an important part of the extrinsic regulatory mechanism, which has been shown both in vivo (McLennan, 1994;Lefeuvre et al, 1996;Washabaugh et al, 1998), as well as in vitro using co-cultures of the nerve and myotubes (Jiang et al, 2004;Jordan et al, 2005). In addition, maturation and survival of both primary and secondary myotubes are largely dependent on innervation (Hughes and Ontell, 1992;Ashby et al, 1993a,b;Wilson and Harris, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Wnt signaling in fiber type differentiation of mammalian fetal skeletal muscle remains unknown. Although the innervation-dependent extrinsic signals that determine fetal muscle fiber types have started to be uncovered (Jiang et al, 2004;Jordan et al, 2003Jordan et al, , 2005, the intrinsic and innervationindependent extrinsic factors that regulate initial fiber types of fetal muscle have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…A mutagenesis study (19) has indicated that both NFAT and MEF2 binding sites are required for innervation-induced MyHC2 promoter activity in slow muscle fibers. Basically, there is NFAT activation by RyR inhibition (20), whereas IP3R blockade results in the opposite effect (21).…”
Section: Discussionmentioning
confidence: 99%
“…This construct has been previously characterized (Jiang et al, 2004). NFAT and MEF2 sensor constructs containing multimerized NFAT and MEF2 binding sites, respectively, coupled to the luciferase gene (3 µg/35 mm dish) were kindly provided by E. Olson (University of Texas Southwestern Medical Center, Dallas, TX).…”
Section: Dna Transfectionsmentioning
confidence: 99%
“…The fast MyHCIIa promoter was activated by increased calcium, NFAT and MEF2 (Allen and Leinwand, 2002). The avian slow MyHC2 promoter in slow muscle fibers is activated by both NFAT and MEF2, and both are required for innervationinduced expression of the slow muscle fiber phenotype (Jiang et al, 2004). Furthermore, regulation of NFAT transcriptional activity was fiber-type dependent.…”
Section: Introductionmentioning
confidence: 99%